Reconstrução categorial de O Capital à luz de seus esboços: a instauração da crítica da economia política (1857, 1863) - Leonardo Gomes de Deus (2010)
The work studies some of the manuscripts written by Karl Marx from 1857 until 1863, especially the Grundrisse and the Economic Manuscript of 1861-1863. By the presentation of the most important categories developed in those works, it demonstrates the thesis that the marxian critique of political economy acquired its main features and its own specificity during the period.